Isolation, identification and characterization of dehalogenase producing bacteria isolated from Labeo Rohita and its environment - Rosland Abel, Stasha Eleanor (2012)
Microbial dehalogenases are involved in the biodegradation of many types of halogenated compounds. The presence of halogenated compounds in water does not only suppress the immune system of fish but adversely induces serious morbidity and mortality among cultured stocks. In this study, we attempted to screen the gut of pond-reared rohu (Labeo rohita) for isolating dehalogenase gene bacteria using molecular technique and tested the degradation ability in vitro. The present study shows eight bacterial strains studied were identified as Enterobacter mori (MK121001), Enterobacter cloacae (MK121003), Enterobacter cloacae (MK121004), Enterobacter cloacae (MK121010), Ralstonia solanacearum (121002), Acinetobacter baumannii (MK121007), Chromobacterium violaceum (MK121009) and Pantoea vagans (121011). Further analysis found three bacterial strains (MK121002, MK121007 and MK121009) were capable of degrading 2,2- dichloropropionic acid (2,2-DCP) as the sole carbon source up to a final substrate concentration of 20 mM. Their mean growth doubling time ranging from 6-23 h with the maximum of chloride ion released of 85%. Another bacterium was isolated from soil samples collected from lake water at Universiti Teknologi Malaysia, Skudai also capable of degrading 2,2-DCP. Phylogenetic analysis indicated that Serratia marcescens SE1 strain clearly shared 97% homology to the genus of Serratia marcescens according to bioinformatics analysis. Serratia marcescens has the ability to degrade 2,2-DCP with cells doubling time of 5 h and maximum chloride ion released of 38 µmolCl-/mL in the liquid growth medium.